Traditionalization Effect and Maternal Gatekeeping: Too Old Answers to Old Questions of Equality in Family Education (KULT_online, 2012)
The bioscientifically informed study by education scholar Annette Mennicke aims at providing "surprising answers to old questions" with respect to equality issues in family education. Against the background of current debates on women's participation in the workforce and according measures – including a mandatory female quota or parental subsidies – the author outlines contexts, reasons, and consequences of (primarily) the lack of paternal participation in active parental leave. By means of sociobiological findings Mennicke nominates the return to traditional gender roles in transition to parenthood and the child-care monopoly claimed by protective mothers as major reasons for this uneven involvement. She subsequently identifies an evolutionarily related divide between mating effort and parenting effort that eventually leads to the persistence of (binary) gender roles. Based on her results the author conclusively proposes anything but new and unassailable perspectives for parental education and the advance of fathers' investment.